Graphene oxide nanoplatelets composite membrane with hydrophilic and antifouling properties for wastewater treatment - Lee, Jaewoo (2017)
As a potential remedy for the water shortage, membrane bioreactor (MBR) has emerged and attracted much attention in the field of wastewater treatment and reuse. However, MBRs have membrane fouling which is the major obstacle in maximizing their efficiency leading to short membrane lifetime and high operating costs. Here we demonstrate that the nanoplatelets of graphene oxide included in the preparation of membrane suppress the fouling to such an extent that a fivefold lengthening is achieved of the time between chemical cleanings. It was quite a surprise to discover that inclusion of only about 1 wt% of graphene oxide in the fabrication of membrane could spring up a new generation of membrane with anti-fouling capability for MBRs. Utilization of graphene oxide introduced here for wastewater treatment would open and facilitate graphene-based environmental applications.